TOLERANCE TOWARDS LGBT INDIVIDUALS AMONG MALAYSIANS - LING, Hsin-Nie; Ting, Su Hie (2021)
Of late, Lesbian, Gay, Bisexual and Transgender (LGBT) has made its presence felt in Malaysian society. The study examined tolerance towards LGBT individuals among Malaysians. Questionnaire data were collected from 411 respondents consisting of different age, ethnicity, and religion groups. The results indicate that a majority of the respondents felt that heterosexuality is the best because of religion and morality. There was some agreement that LGBT individuals should be counselled so that they can overcome their feelings of wanting to be LGBT and return to being either male or female. However, at the same time, the respondents somewhat believed that people are born with LGBT tendencies and they need not keep their sexual orientation a secret. The respondents agreed that LGBT individuals can fit into society, and LGBT in itself is not a problem but society makes it a problem. Interestingly, the respondents were open to LGBT individuals standing up for their rights. They also agreed to some extent that LGBT individuals can live the life they want to live, including adopting a child, dating and living with whoever they want, and expressing their views on Malaysian television channels. The results suggest some tolerance towards LGBT existence in society.